Odpowiedzi

Najlepsza Odpowiedź!
2010-03-14T12:13:00+01:00
(-2i2/5)*(-33/4)= (- 12/5) *( - 15/4) = 9
(-2i2/3)/1,2= ( - 8/3) / 12/10 = ( - 8/3) * 10/12 = - 2 2/9
2/3/(-6)= 2/3 * ( - 1/6) = - 1/9
(-0,45)/1i4/5= ( - 45/100) / 9/5 = (- 9/20) * 5/9 = - 1/4


2010-03-14T12:14:47+01:00
A) (-2i2/5)*(-33/4)= 19,8
b) (-2i2/3)/1,2= (-2i2/9)
c) 2/3/(-6)= (-1/9
d) (-0,45)/1i4/5=(-4)
2010-03-14T12:15:59+01:00
(-2i2\5)(-33\4)=(-12\5)(-33\4)=396\20=19,8
(-2i2\3)\1,2=(-8\3)\(12\10)=(-8\3)*(10\12)=-80\36=-2i2\9
(2\3)\(-6)=(2\3)*(-1\6)=-2\18=-1\9
(-0,45)\1i4\5=(-45\100)\(9\5)=(-45\100)*(5\9)=-225\900=1\4